2019
DOI: 10.1111/jonm.12762
|View full text |Cite
|
Sign up to set email alerts
|

Association of cumulative job dissatisfaction with depression, anxiety and stress among expatriate nurses in Saudi Arabia

Abstract: Aims We aimed to (a) determine the prevalence of depression, anxiety and stress among expatriate nurses in Saudi Arabia, and (b) assess how dissatisfaction with salary, workload and teamwork, individually and in combination, was associated with those conditions. Background Prevalence estimates for depression, anxiety and stress among nurses are higher than those in the general population. Available data on the mental health of expatriate nurses are limited. Methods Expatriate nurses (n = 977) from governmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 49 publications
3
51
0
Order By: Relevance
“…Some studies revealed that, for medical workers, the smaller payoff and the greater giving may cause the heavier anxiety symptoms. 27,28 During the epidemic of COVID-19, medical workers were on the front line of fighting against the virus, and at a high risk of infection at any time. Therefore, if welfare treatment is not improved to some extent, it may tend to induce anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies revealed that, for medical workers, the smaller payoff and the greater giving may cause the heavier anxiety symptoms. 27,28 During the epidemic of COVID-19, medical workers were on the front line of fighting against the virus, and at a high risk of infection at any time. Therefore, if welfare treatment is not improved to some extent, it may tend to induce anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, they may feel disrespected and reprimanded, which leads to them experiencing work stress. Saquib studied the nurses working at two government hospitals in KSA and found that migrant nurses face heavy workload and uncooperative colleagues, which cause them to experience medical errors, anxiety, and stress 11 . Additionally, acute health care centers are strategically located across the country to deliver preventative and curative services.…”
Section: Introductionmentioning
confidence: 99%
“…Also, a recent study in Saudi Arabia found that depression, anxiety and stress among nurses are higher than of those in the general population, in addition to the shortage of nurses. Work-related stress compromises quality of care and leads to burnout, turnover and job dissatisfaction (6,(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%